The Economics of Non-Tariff Measures: A Primer - Jaime de Melo; Ben Shepherd (Fondation pour les études et recherches sur le développement international (FERDI), 2018)
This paper takes the non-tariff measures (NTMs) codified and collected under the MAST (Multi-Agency Support Team) typology to study their economic effects, concentrating on the effects on prices, quantities and welfare. To this end, NTMs are categorized into six groups (tariff-like measures, quantitative restrictions, subsidies, rules of origin, frictional barriers to trade and standard-like measures). The effects of NTMs in each of these groups are then studied, relying on a partial equilibrium model under perfect competition where a diagrammatic presentation is mostly used to describe the effects of each category of NTM on prices, quantities produced, quantities traded, and welfare. The paper then reviews several case studies for developing countries, focusing both on the methodology used and on results.
Keywords: 330; Non-tariff measures